Applicability of evaluation instruments and techniques according to the competence model of MEDUCA to assess the speaking area of the english program at Junior High School Level at I.P.T. Arnulfo Arias Madrid High School. David, Chiriquí 2013 - Aizpurúa, Ayleen (UDELAS, 2013)
This research has an importan goal, it consists in achieve a good use of the evaluation instruments for teaching at junior school. Also, it contains some information of the defferent types of evaluation instruments and ways how to use them. Summarizing, this is a good tool in order to enjoy the process of english learning as a second language.